(untitled) (GEOmedia, 2019)
Galileo and Copernicus are not only flagship technology programs of the European Union: they can be the ambassadors of European cooperation in other continents, an effective opportunity for growth and development together. On February 14th and 15th this year, a post-graduate course on satellites technologies and applications was held in Santo Domingo, Dominican Republic, at the Universidad Nacional Pedro Henràquez Ureña (UNPHU).